Jawabanmu

2014-05-02T17:05:55+07:00
G(-3)= p(-3)+q=-4 |-3p+q=-4   Selanjutnya g(2)= p(2)+q=11| 2p+q=11

-3p+q=-4                                                  g(1)= px+q= 3(1) +5= 8
2p+q=11                                                   JAwabannya adalah 8
________-
-5p=-15               -3(3)+q=-4
p =3                   -9+q=-4
                          q=-4+9
                          q=5
2014-05-02T17:08:49+07:00
G(x)=px+q

g(-3)=p(-3)+q=-4
=-3p+q=-4..........(1)
g(2)=2p+q=11......(2)

-3p+q=-4 - 2p+q=11 (eliminasi)
-3p-2p+p-p=-4-11
-5p=-15
p=-15/-5
p=3...

2(3)+q=11
6+q=11
q=11-6=5

dik: p=3 dan q=5
maka g(1)=3(1)+5
=3+5=8

gitu.....